Long‐term low‐temperature hot corrosion of PTA welded René 41 superalloy under marine‐like conditions. Issue 9 (3rd May 2022) - Hempel, Christian; Mandel, Marcel; Schimpf, Christian; Krüger, Lutz
Abstract: The hot corrosion behavior of plasma transferred arc (PTA) welded René 41 in NaCl, NaVO3, Na2 SO4, and a salt mixture of 87.5 wt% Na2 SO4 + 5 wt% NaCl + 7.5 wt% NaVO3 was investigated at 600°C. The single‐salt experiments were carried out to identify specific corrosion characteristics and to provide insights into and, thus, an understanding of the corresponding corrosion processes. NaVO3 and NaCl showed strong corrosive effects, while Na2 SO4 proved less corrosive. Long‐term experiments were carried out to simulate real machine operating conditions. After cyclic studies with repeated changes in temperature, the deep and local corrosive attack became apparent, which is characteristic for low‐temperature hot corrosion. Abstract : The long‐term, low‐temperature hot‐corrosion behavior of a plasma transferred arc‐welded René 41 superalloy under marine‐like conditions is investigated in this study. After a combination of energy‐dispersive X‐ray spectroscopy and X‐ray diffraction analyses, a reaction mechanism is derived in association with thermodynamic calculations. Furthermore, the differences between cyclic and isothermal studies are compared and discussed.